2013
DOI: 10.1371/journal.pone.0065209
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing and De Novo Analysis of a Cytoplasmic Male Sterile Line and Its Near-Isogenic Restorer Line in Chili Pepper (Capsicum annuum L.)

Abstract: BackgroundThe use of cytoplasmic male sterility (CMS) in F1 hybrid seed production of chili pepper is increasingly popular. However, the molecular mechanisms of cytoplasmic male sterility and fertility restoration remain poorly understood due to limited transcriptomic and genomic data. Therefore, we analyzed the difference between a CMS line 121A and its near-isogenic restorer line 121C in transcriptome level using next generation sequencing technology (NGS), aiming to find out critical genes and pathways asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 70 publications
6
48
0
1
Order By: Relevance
“…The only source of CMS in this species is S cytoplasm from the ‘PI 164835’ line introduced from India (Peterson , Liu et al. ). Kim and Kim () developed two CMS‐specific SCAR markers to distinguish N cytoplasm from S cytoplasm by PCR.…”
Section: Pollination Control Methods In Different Vegetable Cropsmentioning
confidence: 99%
“…The only source of CMS in this species is S cytoplasm from the ‘PI 164835’ line introduced from India (Peterson , Liu et al. ). Kim and Kim () developed two CMS‐specific SCAR markers to distinguish N cytoplasm from S cytoplasm by PCR.…”
Section: Pollination Control Methods In Different Vegetable Cropsmentioning
confidence: 99%
“…Furthermore, partial fertility restoration has been reported (Lee, 2001;Lee and Park, 2008) with multiple haplotypes in existence (Min et al, 2008). Liu et al (2013) found differential expression of several PPR genes between near-isogenic lines for Rf and CMS in chile pepper. Although most Rf genes have been found to encode PPR proteins, some non-PPR genes have been identified to be closely associated with restoration-of-fertility in chile pepper.…”
mentioning
confidence: 90%
“…Recently, the transcriptome profiles of sterile lines and their fertility restorers have been investigated in various species during specific developmental stages, thereby demonstrating that a large number of differentially expressed genes (DEGs) participate in many metabolic pathways, e.g., in Brassica napus (An et al, 2014), cotton (Suzuki et al, 2013), cabbage (Wang et al, 2016), chili pepper ( Capsicum annuum ) (Liu et al, 2013), kenaf (Chen et al, 2014), watermelon (Rhee et al, 2015), radish (Mei et al, 2016), rice (Bai et al, 2015), and Welsh onion (Liu et al, 2016). However, the complexity of the wheat genome and the lack of complete reference genome mean that transcriptome sequencing in male sterile wheat remains difficult.…”
Section: Introductionmentioning
confidence: 99%